APPLICATION OF THE INSIDE OUTSIDE CIRCLE COOPERATIVE LEARNING MODEL TO THE PYTHAGOREAN THEOREM M ATERIAL OF SMP NEGERI 13 BANDA ACEH STUDENTS - AG, Burhanuddin; Permana, Fithri Angelia; Asri, Khairul; Mukhtasar, Mukhtasar; Andalia, Nurlena (English Education Department, 2023)
The purpose of this study is to determine the Implementation of the Inside Outside Circle Cooperative Learning Model on Pythagorean Theorem Material for Students of SMP Negeri 13 Banda Aceh. The method used in this study is a quasi-experimental research method. The research design used was one group pre test-post test design. This research was conducted at SMP Negeri 13 Banda Aceh and was carried out on December 11, 2023 in class VIII in the odd semester of the 2022/2023 academic year. The population in this study was all 31 students of Class VIII SMP Negeri 13 Banda Aceh. While the sample is class VIII-5 consisting of 31 students. Most students obtained grades greater than or equal to KKM scores, with an average score of 87.56. From the analysis of the t test, it was calculated that it was 3.82 greater than the table t. This shows that the Inside Outside Circle model affects the learning outcomes of Pythagorean Theorem material for grade VIII students of SMPN 13 Banda Aceh. The implementation of the Inside Outside Circle Cooperative Learning Model on the Pythagorean Theorem material grade VIII SMPN 13 Banda Aceh achieved maximum learning completeness. This model is very good to be applied to the teaching and learning process, because it can stimulate students to concentrate on the material being studied